Slum priests in present-day Argentina: between the Third World Catholic heritage and Pope Francis (Tempo e Argumento, 2021)
This article aims to contribute to the discussion on the history of priestly groups in Latin America, particularly in Argentina, from a historical perspective that takes into account the relations of continuity and rupture between the Movement of Priests for the Third World (Movimiento de Sacerdotes para el Tercer Mundo [MSTM]), which operated actively between the late 1960s and mid-1970s, and the group of current slum priests referred to in the figure of Pope Francis. We are interested in giving an account of a comparative journey between his pastoral, ecclesial, and political options and his theological affiliation. This is an examination that takes up the proposals of my doctoral research study on the ‘Third World constellation’ in Argentina, showing that such a constellation received the theological influence of the Popular Pastoral or Theology of the People (TP), which was the Argentine version of Liberation Theology (LT), but in a culturalist rather than classist key and with elements closer to clerical paternalism and populist practices, where the ‘preferential option for the poor’ and the ‘option for Peronism’ converged. Far from having perished, this current is currently manifested in the postulates of Pope Francis and the slum priests in the City of Buenos Aires. Our work methodology has preferably a qualitative nature and it is supported by specialized bibliography on the theme, ecclesiastical documents, theological books, oral interviews, and analysis of written press articles and audiovisual sources.Keywords: slum priests; third world priests; theology of the people; Pope Francis; populism.